The effects of volcanism on Oligocene-age plant communities from the Ethiopian Plateau, and implications for vegetational resilience in a heterogeneous landscape - García Massini, Juan Leandro (2011)
Substantial volcanism and associated volcaniclastic sedimentation took place in association with East African Rift formation, and in some cases this would have had substantial ecological impacts. Ethiopian Late Oligocene (27.36 ± 0.11. Ma) fossiliferous volcanogenic strata provide opportunities to evaluate the magnitude of disruptive impact of volcanism on forest communities (before development of the Main Ethiopian Rift), and to assess their resilience. Fine-scale sampling and palynological analyses from the Magargaria River region of the northwestern Ethiopian Plateau tests the hypothesis that volcanism had a regional and significant disrupting effect on forest vegetation. These studies are compared with macrofossil and sedimentological data representing more local conditions previously reported from the same sediments. Results indicate that while some forests gave way to open environments dominated by herbaceous taxa, other communities remained or recovered quickly. Volcanic influences on sedimentary processes altered an existing forest ecosystem by creating a spatially heterogeneous landscape that also varied through time. This study supports the inherent significance of palynological data as indicators of ecological change at a regional scale relative to the more local view that macrofossils can provide, and underscores the importance of both kinds of fossils whenever possible for the study of the ecological dynamics of plant communities. The presence of forest taxa after repeated ashfalls indicates a degree of forest community resilience consistent with relatively limited burial by ash during the studied volcanic episodes. This study also suggests that taphonomic and diagenetic processes strongly affected the composition of palynomorph assemblages, skewing them towards thick-walled individuals, especially fungi.